2017
DOI: 10.1093/gigascience/gix023
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide sequencing of longan (Dimocarpus longan Lour.) provides insights into molecular basis of its polyphenol-rich characteristics

Abstract: Longan (Dimocarpus longan Lour.), an important subtropical fruit in the family Sapindaceae, is grown in more than 10 countries. Longan is an edible drupe fruit and a source of traditional medicine with polyphenol-rich traits. Tree size, alternate bearing, and witches' broom disease still pose serious problems. To gain insights into the genomic basis of longan traits, a draft genome sequence was assembled. The draft genome (about 471.88 Mb) of a Chinese longan cultivar, “Honghezi,” was estimated to contain 31 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 84 publications
(171 reference statements)
9
140
3
Order By: Relevance
“…These genes included 58 DlWRKYs , which were also found by Lin et al [37], and one gene Dlo_ 022548.1 ( DlWRKY 36) found in our study. Finally, after the WRKY domain scanning and sequence alignment, 55 DlWRKY genes were determined in the longan genome (Table 1).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These genes included 58 DlWRKYs , which were also found by Lin et al [37], and one gene Dlo_ 022548.1 ( DlWRKY 36) found in our study. Finally, after the WRKY domain scanning and sequence alignment, 55 DlWRKY genes were determined in the longan genome (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, the successful genome sequencing of longan makes it possible to analyze WRKY TFs at the whole-genome level [37]. The present study is the first to identify and characterize WRKY proteins from whole-genome sequences of longan.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Clean reads were mapped to the longan reference genome using the Bowtie2 method . The expression level of genes and transcripts was calculated using RNA‐Seq by Expectation–Maximization (RSEM) software .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the high‐throughput sequencing of agarwood showed that genes associated with secondary metabolism were regulated under red light/far‐red conditions linked to the regulation of miRNAs . However, many studies on plant RNA‐seq revealed that the related miRNAs of light regulated metabolism were different in different species . It is therefore also necessary to investigate how the miRNAs respond to light in longan ECs by RNA‐seq.…”
Section: Introductionmentioning
confidence: 99%